Examining Students’ Responses to Literary Texts in a Malaysian ESL Classroom Context: A Case Study of Secondary Schools in Sarawak - Esther, anak John Perry (Universiti Malaysia Sarawak, (UNIMAS), 2019)
Numerous studies have explored students’ responses to literary texts in the language classroom and the variety of factors that shape them. Reader-response approach is one of the approaches in the field of literary criticism that has been used in understanding students’ responses to literary texts in schools due to its features that centre on students’ responses. However, more needs to be known about what are the types of responses and the factors that contribute to these responses, given the different classroom contexts in which teaching and learning of literary texts take place. This study sought to meet this need by examining students’ responses to literary texts taught in the Malaysian English as Second Language (ESL) secondary school classroom and their contributing factors. By using the case study method, the study carried out an in-depth, detailed examination of students’ responses to the literary texts taught at secondary schools in the Kuching and Kota Samarahan divisions. The responses were gathered from documents such as students’ written work, assessments scripts, and those recorded with consent during observed lessons. These responses were then analysed using Cox and Many’s and Squire’s models of response to literature to determine their respective nature or type. In order to ascertain the contributing factors, the responses were further analysed along with interview data from both students and teachers, as well as data from the teachers’ observed lessons, their lesson plans and teaching activities. Results show that students mostly engaged in three different types of literary responses that are categorised based on the Squire’s Classification of Responses and Cox and Many 5 Point Efferent to Aesthetic Continuum, namely, Primarily Efferent, Mostly Efferent and Primarily Aesthetic. Interestingly, despite some challenges such as language proficiency and limited reading exposure, some students engaged in creating multiple responses to a single question or task, showcasing their ability to move along the efferent-aesthetic continuum during or by the end of instruction. The results also show that the production of each of these response types was not only dependent on the lessons planned or the activities carried out by the students’ respective teachers, but also influenced by many interrelated factors namely individual, textual, contextual and social factors. This reinforces the argument that literary responses are complex and can never be shaped by the text or the reader alone but also from various factors that differ from one student to another which makes each one of them as unique and diversed. The findings from this study may not only provide more insights into the complex production of students’ literary responses but call attention to the need for more understanding of the response type-contributing factor interrelationship that has direct consequences on literature instruction in different classroom contexts.